13 - (Re) making Bodies: The Structures and Dynamics of Aesthetics and Aspirations in an Evolving Africa: Report on the international conference held in Dar es Salam, Tanzania, 3-4, November, 2016 - Onoma, Ato Kwamena (CODESRIA Bulletin, 2021)
Abstract